Antisipasi Didaktis dengan Strategi Scaffolding pada Pembelajaran Barisan dan Deret Aritmetika - Mariyani Mariyani; Nyiayu Fahriza Fuadiah; Allen Marga Retta (Jurnal Elemen, 2021)
This study aims to explain didactic anticipation in learning arithmetic sequences and series. The study was conducted using a didactic design study with three stages: prospective analysis, metapedadidactic, and retrospective analysis. Data were collected through tests, interviews, and documentation. Researchers compile HLT based on the analysis of learning constraints for students in learning arithmetic sequences and series. From the HLT, a didactic design was designed. The didactic design is implemented with results showing that there are three didactic events that researchers anticipate didactic with a scaffolding strategy, namely: 1) when determining the value that satisfies the number pattern, the researcher anticipates the didactic by providing directions in the form of directions to solve the given problem; 2) when determining the definition and example of arithmetic sequences, the didactic anticipation by the researcher by providing another example of the form of a number sequence makes students better understand the learning given; 3) when determining the value of the nth term and the sum of the first n terms of an arithmetic sequence and series, the didactic anticipation is given namely with their respective shirts to check their work and make direct interactions. The didactic anticipation that the researchers gave in this study was adjusted to the conditions of the environment around the classroom.